THE MECHANISMS OF PROFESSIONAL POTENTIAL DEVELOPMENT OF CIVIL SERVANTS IN POLAND - Polishchuk I.V. (Pressing Problems of Public Administration, 2015)
The analysis of modernization processes connected to the professionalization of civil service in Poland through history has been done. Key principles for the professional potential development of civil servants in Poland have been designated within the framework of their implementation for the modernization of civil service in Ukraine.